2018
DOI: 10.1016/j.ijadhadh.2017.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Joints with bars glued-in softwood laminated timber subjected to climatic cycles

Abstract: The effect of climatic cycles (extreme temperatures and humidity) on the performance of joints made with threaded steel rods glued by two-component epoxy adhesive in softwood glulam timber is studied. Short-term tests have been made on three types of specimens: standard condition specimens (20 °C/65%RH), specimens subjected to extreme temperature and humidity during its storage in climatic chamber in service load situation, and specimens in similar unloaded situation. The load capacity, the failure modes and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 32 publications
1
1
0
1
Order By: Relevance
“…Differences between EP (T g ≈ 69 C) and PUR (T g ≈ 86 C) are also reported by Verdet et al, 40 whereby both adhesive types lead to similar, almost linear, decreases in strength in the temperature range 30-70 C. 22 Similar results are also reported by di Maria et al, 41 showing a 50% reduction in load-bearing capacity when T g is exceeded. This effect was also described by Otero-Chans et al 42 However, they found no clear evidence that the strength of the joints tested under normal conditions was affected after exposure to temperatures up to 50 C at a relative humidity φ of more than 80%. Lartigau et al 43 report on tests with bonded bars in the temperature range 20-80 C using an EP (T g = 58 C).…”
Section: Introductionsupporting
confidence: 53%
“…Differences between EP (T g ≈ 69 C) and PUR (T g ≈ 86 C) are also reported by Verdet et al, 40 whereby both adhesive types lead to similar, almost linear, decreases in strength in the temperature range 30-70 C. 22 Similar results are also reported by di Maria et al, 41 showing a 50% reduction in load-bearing capacity when T g is exceeded. This effect was also described by Otero-Chans et al 42 However, they found no clear evidence that the strength of the joints tested under normal conditions was affected after exposure to temperatures up to 50 C at a relative humidity φ of more than 80%. Lartigau et al 43 report on tests with bonded bars in the temperature range 20-80 C using an EP (T g = 58 C).…”
Section: Introductionsupporting
confidence: 53%
“…Hierzu fasst eine Reihe von Übersichtsartikeln [7, 10–12] den aktuellen Konsens über den Stand der Technik zusammen. In diesen Studien werden neben der Berücksichtigung von Laborbedingungen auch Aspekte wie das Verhalten unter Temperatur [13, 14], Ermüdung [15–18], Kriechen [19], verschiedene Umweltbedingungen [20] oder Defekte [21–23] untersucht.…”
Section: Stand Der Technikunclassified
“…Similar results were found for the 12 mm dia. threaded steel rods glued into softwood with a two-component epoxy adhesive (HILTI HIT-RE 500) by Otero-Chans et al (2018).…”
Section: Introductionmentioning
confidence: 99%